Prevalence of Bronchial Asthma in Children in Southern Kyrgyzstan - Jumanalieva, Maksudakan (International Journal of Child Health and Nutrition, 2024)
Background: The aim of this study was to investigate the prevalence of bronchial asthma and other allergic diseases such as allergic rhinitis and atopic dermatitis among 6075 school-aged children in Osh, Jalal-Abad and Batken regions of Kyrgyzstan. Methods: 6075 children were questioned using the ISAAC questionnaire. Bronchial asthma symptoms are frequent – 21.1% of children had difficulty wheezing, and 13.4% had night cough. This indicates a high prevalence of bronchial asthma among children in the study population. The obtained morbidity rates significantly exceed the official statistics for the region. This indicates insufficient diagnosis of allergic diseases in children and substantiates the need to develop a set of measures aimed at optimizing the detection of cases of allergic pathology and increasing the effectiveness of therapeutic and preventive measures. Results: The results of the study demonstrate a high need for the development and implementation of a regional program for the diagnosis, treatment, and prevention of allergic diseases in children of Osh, Jalal-Abad, and Batken regions. Conclusion: Implementing such a program will contribute to better control of bronchial asthma and other allergic pathologies and improve the quality of life of the child population in the region.